Implementation of Universal Newborn Screening for Severe Combined Immunodeficiency in Singapore While Continuing Routine Bacille-Calmette-Guerin Vaccination Given at Birth - Chan, Su-Wan Bianca; Zhong, Youjia; Lim, Soon Chuan James; Poh, Sherry; Teh, Kai Liang; Soh, Jian Yi; Chong, Chia Yin; Thoon, Koh Cheng; Seng, Michaela; Tan, Ee Shien; Arkachaisri, Thaschawee; Liew, Woei Kang (Frontiers in Immunology, 2022)
Introduction: Severe Combined Immunodeficiency (SCID) is generally fatal if untreated; it predisposes to severe infections, including disseminated Bacille-Calmette-Guerin (BCG) disease from BCG vaccination at birth. However, delaying BCG vaccination can be detrimental to the population in tuberculosis-endemic regions. Early diagnosis of SCID through newborn screening followed by pre-emptive treatment with anti-mycobacterial therapy may be an alternative strategy to delaying routine BCG vaccination. We report the results of the first year of newborn SCID screening in Singapore while continuing routine BCG vaccination at birth. Method: Newborn screening using a T-cell receptor excision circle (TREC) assay was performed in dried blood spots received between 10 October 2019 to 9 October 2020 using the Enlite Neonatal TREC kit. Patients with low TREC had lymphocyte subset analysis and full blood count performed to determine the severity of lymphopenia and likelihood of SCID to guide further management. Results: Of the 35888 newborns screened in 1 year, no SCID cases were detected, while 13 cases of non-SCID T-cell lymphopenia (TCL) were picked up. Using a threshold for normal TREC to be >18 copies/μL, the retest rate was 0.1% and referral rate to immunologist was 0.04%. Initial low TREC correlated with low absolute lymphocyte counts (ALC), and subsequent normal ALC corresponded with increases in TREC, thus patients with normal first CD3+ T cell counts were considered to have transient idiopathic TCL instead of false positive results. 7/13 (54%) had secondary TCL (from sepsis, Trisomy 21 with hydrops and stoma losses or chylothorax, extreme prematurity, or partial DiGeorge Syndrome) and 6/13 (46%) had idiopathic TCL. No cases of SCID were diagnosed clinically in Singapore during this period and for 10 months after, indicating that no cases were missed by the screening program. 8/9 (89%) of term infants with abnormal TREC results received BCG vaccination within the first 6 days of life when TREC and ALC were low. No patients developed BCG complications after a median follow-up of 17months. Conclusion: Newborn screening for SCID can be implemented while continuing routine BCG vaccination at birth. Patients with transient TCL and no underlying primary immunodeficiency are able to tolerate BCG vaccination.